Otodectes cynotis (Acari: Psoroptidae) infestations in Southern pudus (Pudu puda): In situ and ex situ data of an unexpected host-parasite record - Caroline Wilhelm; Edwin Kniha; Pamela Muñoz; Ángelo Espinoza; Laura Platner; Saskia Dreyer; Lisa Grund; Zoë Tess Lara Lindhorst; Ulrich Gärtner; Julia Walochnik; Anja Taubert; Dominik Fischer; et al. (International Journal for Parasitology: Parasites and Wildlife)
Otodectes cynotis (Acari: Psoroptidae) constitutes an obligate, non-burrowing ectoparasite and causes otodectic mange primarily in domestic and wild carnivores. Only few studies have described this parasite in herbivore hosts so far. In the current study, we report O. cynotis infestations in Southern pudus (Pudu puda), categorized in the IUCN red list as near threatened. Otodectes cynotis was detected in free-ranging animals in Chile (in situ), as well as in zoo-housed pudus at the Zoo Wuppertal, Germany (ex situ). During clinical work, two free-ranging pudus temporarily rehabilitated at the Centro de Rehabilitación de Fauna Silvestre (CEREFAS), Valdivia, Chile, were observed with low to moderate yellowish-brown secretions and encrustations inside the pinna and external auditory canal accompanied by an inflammatory Otitis externa. Analysis via light microscopy exhibited the presence of mange mites, which were identified as O. cynotis via morphological characteristics and molecular analysis. At the Zoo Wuppertal, ear mites were detected in 15 pudus between 2015 and 2024, however, a definite species identification (O. cynotis) was carried out in 4 animals within the current study between 2023 and 2024. Some affected pudus showed bald spots around the ears and the head and exhibited headshaking behavior, whilst others were asymptomatic. In some cases, mites were found as a secondary finding when clinical examination under general anesthesia was performed for other reasons. To the best of our knowledge, this signifies the first report of O. cynotis infestations in pudus by combining morphological and molecular identification. We here present clinical in situ and ex situ data and show that zoological gardens and widlife rehabilitation centers play an important role in research and monitoring of neglected wildlife diseases.